Digitalization of Urban Tourism Innovation for Increasing Local Government Revenue - Afrinady Rustam; Asrinaldy Asrinaldy; Hendri Koeswara; Kamaruddin Kamaruddin (CV. Austronesia Akademika, 2025)
Urban tourism has emerged as a strategic driver of local economic development, yet cities face mounting challenges in translating tourism growth into measurable fiscal benefits. The proliferation of digital technologies ranging from smart ticketing systems and destination platforms to analytics-based governance presents opportunities for cities to enhance efficiency, transparency, and revenue capture. This study aims to examine how the digitalization of urban tourism innovation contributes to increasing local government revenue (LGR) through improved compliance, reduced leakage, and the formalization of tourism transactions. Using a Systematic Literature Review (SLR) approach, the research synthesizes empirical and conceptual studies from multidisciplinary fields including urban tourism, smart city governance, and public finance. Literature was systematically searched, screened, and analyzed to identify mechanisms linking digital innovation with fiscal performance. The findings reveal four dominant revenue pathways: (1) expanding the taxable base through transaction formalization, (2) enhancing compliance and auditability via digital payments and e-licensing, (3) reducing administrative and operational inefficiencies through automation and analytics, and (4) protecting long-term fiscal sustainability by improving destination management and visitor dispersion. The results highlight that fiscal gains materialize when digitalization initiatives are embedded within coherent governance frameworks and data-sharing mechanisms across public agencies and private actors. The study concludes that urban tourism digitalization can be a strategic fiscal instrument transforming cities into more efficient, accountable, and sustainable tourism ecosystems while strengthening their local revenue capacity.